2005
DOI: 10.1111/j.1365-313x.2005.02350.x
|View full text |Cite
|
Sign up to set email alerts
|

The stability of the Arabidopsis transcriptome in transgenic plants expressing the marker genes nptII and uidA

Abstract: SummaryThe ATH1 Arabidopsis GeneChip from Affymetrix was used to search for transcriptome changes in Arabidopsis associated with the strong expression of transgenes regulated by constitutive promoters. The insertion and expression of the commonly used marker genes, uidA and nptII, did not induce changes to the expression patterns of the approximately 24 000 genes that were screened under optimal growth conditions and under physiological stress imposed by low temperatures. Approximately 8000 genes (35% of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 30 publications
3
64
1
Order By: Relevance
“…An understanding of the unintended effects of genes (Cellini et al ., 2004) and drought (El Ouakfaoui and Miki, 2005). These data show that transgenic plants created with these marker genes are transcriptionally identical to non-transgenic plants.…”
Section: Introductionmentioning
confidence: 52%
“…An understanding of the unintended effects of genes (Cellini et al ., 2004) and drought (El Ouakfaoui and Miki, 2005). These data show that transgenic plants created with these marker genes are transcriptionally identical to non-transgenic plants.…”
Section: Introductionmentioning
confidence: 52%
“…Toxic effects are not expected from metabolites of transgenic GUS activity in plants (Gilissen et al, 1998). As with nptII, Ouakfaoui and Miki (2005) reported no phenotypic or genetic expression changes of 24,000 genes in transgenic Arabidopsis plants containing the uidA gene. Potential risks of horizontal gene transfer: As with the other markers, genes originally isolated from E. coli (nptII, hph and manA), the uidA gene and the GUS enzyme are widely distributed in the environment, are present in the intestinal tract of vertebrates, including man and are present in food.…”
Section: Reporter Genes Uida (Gus): β-D-glucuronide Glucuronoso-hydromentioning
confidence: 99%
“…In 2004, the Scientific Panel on genetically modified organisms (GMO Panel) of the European Food Safety Authority (EFSA) concluded that after 13 years of safe use and careful evaluation, there is no rationale for restricting the use of nptII as a selectable marker for either field studies or commercialization of crop plants containing the protein (European Food Safety Authority, 2004). Pleiotropic effects: Enhancement of physiological fitness due to pleiotropic effects of nptII has not been documented (Miki and McHugh, 2004), and expression of nptII in Arabidopsis had no functional effect on the expression of 24,000 other genes studied (Ouakfaoui and Miki, 2005).…”
Section: Safety Assessment Of Nptiimentioning
confidence: 99%
See 1 more Smart Citation
“…To my knowledge, there is no published, validated research showing any fundamental biochemical or biophysical difference between DNA recombined in a test tube vs. that recombined in a living cell. (2) Compared to other breeding techniques, targeted DNA manipulations achieved during transgenesis, cisgenesis, intragenesis, or genome editing are no more disruptive-and are commonly less disruptive-to a plant's genome, transcriptome, proteome, and composition than other methods of crop improvement [170,171,[195][196][197][198][199][200]. If unanticipated health consequences from GE manipulations merit concern, so do the unanticipated health consequences of each new conventionally bred crop variety [201].…”
Section: Consumption Of Ge Cropsmentioning
confidence: 99%